Literature as a tool to nurture creativity and active reading: read-a-thon with SK Desa Jaya - Abas, Nadhratunnaim; Abdul Aziz, Roslina (Universiti Teknologi MARA, 2009)
Lack of exposure to reading materials in English may affect second language learners' proficiency in the language. This limited exposure could be contributed by not having adequate and most importantly interesting reading materials in English. Aware of this situation, the Academy of Language Studies, UiTM Pahang felt that there was an urgent need to conduct an English Reading Programme, namely Read-a-Thon, for fifty Year Four, Five and Six Students of SK Desa Jaya. This event was part of an annual community service programme held in the UiTM Jengka Campus in September 2006. The students were taught two modules (Reading Poems and Reading a Short Story) and assigned to participate in four indoor activities (Shape-It!, Topsy-Turvy, Act-It-Out and Finders Keepers). A set of questionnaire to evaluate the programme was distributed at the end of the programme. Overall, the feedback received was positive